2022
DOI: 10.1002/anie.202207063
|View full text |Cite
|
Sign up to set email alerts
|

Facile Conversion of α‐Amino Acids into α‐Amino Phosphonates by Decarboxylative Phosphorylation using Visible‐Light Photocatalysis

Abstract: Amino phosphonates exhibit potent inhibitory activity for a wide range of biological processes due to their specific structural and electronic properties, making them important in a plethora of applications, including as enzyme inhibitors, herbicides, antiviral, antibacterial, and antifungal agents. While the traditional synthesis of α-amino phosphonates has relied on the multicomponent Kabachnik-Fields reaction, we herein describe a novel and facile conversion of activated derivatives of α-amino acids directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Combining these results with the literature precedents, [ 7,12,26 ] a plausible mechanism for the radical cascade fragmentation is illustrated in Scheme 5c. Initially, Ag(I) species is oxidized by terminal oxidant K 2 S 2 O 8 to give reactive Ag(II) species which convert carboxylate 12 , generated by the deprotonation of acid with 2,6‐lutidine, into the intermediate carboxyl radical I via a single electron‐transfer(SET) process.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Combining these results with the literature precedents, [ 7,12,26 ] a plausible mechanism for the radical cascade fragmentation is illustrated in Scheme 5c. Initially, Ag(I) species is oxidized by terminal oxidant K 2 S 2 O 8 to give reactive Ag(II) species which convert carboxylate 12 , generated by the deprotonation of acid with 2,6‐lutidine, into the intermediate carboxyl radical I via a single electron‐transfer(SET) process.…”
Section: Resultssupporting
confidence: 77%
“…These results imply that the acyloxy radical intermediate might undergo decarboxylation and ensuing β ‐fragmentation to give olefin 3p' and phenylthio radical. [ 12 ] The latter reacted with 2 to produce 3p" (see the Supporting Information for the reaction mechanism). On the other hand, methionine 1q was subjected to decarboxylative cyanomethylation to give lactone 3q' instead of the desired nitrile 3q .…”
Section: Resultsmentioning
confidence: 99%
“…In order to demonstrate the synthetic utility of our method toward druglike molecules, we carried out a two-step transformation to synthesize phospholeucine, an effective inhibitor of leucine aminopeptidase . Commercially available diethylphosphite 2t reacted smoothly with substrate 1n under otherwise identical conditions, providing the corresponding product 3nt in 58% isolated yield with 91% ee.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of spirocyclic scaffolds into lead structures is also of broad interest in medicinal chemistry; however, it is often accompanied by increased synthetic effort. 73,74 We found that the annulation protocol also offers a straightforward route to ⍺-substituted spirocyclic tetrahydrofurans in serviceable yields (27)(28)(29). Here, we highlight pyrrolidine 23 and tetrahydrofuran 29 as examples of nitrogen-and oxygen-containing analogues of otherwise-identical spirocyclic scaffolds.…”
mentioning
confidence: 91%